ISLAM DAN DEMOKRASI: STUDI KOMPARATIF ANTARA TEORI POLITIK ISLAM DAN DEMOKRASI BARAT - Nul Hakim, Ihsan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
Therelationship between democracy and Islam has been disputed materials among Muslim scholars. One of themsaid that democracy has similar understanding with the concept of Islamic politic, but the other one argued thatboth concepts about politics are different. The present article tries to describe the concept of Islamic politicsand the relation to the democracy. The main question should be answered in this paper is whether the conceptof democracy is equal to Islam or even in dispute. In one side, democracy as a governmental system is not inline with Islam because it does not mention clearly certain formulation of state. Otherwise, having humanityvalues, the democracy has similar concept to Islam because the values and the principles of politic gathered bydemocracy are not contradiction to the principles of Islamic politics.